ByzRev 06.2022.022: Panagiotis Ch. Athanasopoulos (ed.), Translation Activity in the Late Byzantine World.: Contexts, Authors, and Texts (Byzantinisches Archiv, Series philosophica 4). Berlin – Boston: Walter de Gruyter 2022. - Bara, Péter (The Byzantine Review, 2024)
Panagiotis Ch. Athanasopoulos (ed.), Translation Activity in the Late Byzantine World. Contexts, Authors, and Texts (Byzantinisches Archiv, Series philosophica 4). Berlin – Boston: Walter de Gruyter 2022. viii+619 pp., 14 ill., 36 tables. – ISBN 978-3-11-067700-3 (€ 129.95)